Proton conduction in alkali metal ion-exchanged porous ionic crystals. Issue 43 (22nd September 2017) - Uchida, Sayaka; Hosono, Reina; Eguchi, Ryo; Kawahara, Ryosuke; Osuga, Ryota; Kondo, Junko N.; Hibino, Mitsuhiro; Mizuno, Noritaka
Abstract : Li + in an alkali metal ion-exchanged porous ionic crystal forms a dense and extensive hydrogen-bonding network of water molecules with mobile protons leading to a high proton conductivity (>10 −3 S cm −1 ). Abstract : Proton conduction in alkali metal ion-exchanged porous ionic crystals A2 [Cr3 O(OOCH)6 (etpy)3 ]2 [α-SiW12 O40 ]· n H2 O [I-A + ] (A = Li, Na, K, Cs, etpy = 4-ethylpyridine) is investigated. Single crystal and powder X-ray diffraction measurements show that I-A + possesses analogous one-dimensional channels where alkali metal ions (A + ) and water of crystallization exist. Impedance spectroscopy and water diffusion measurements of I-A + show that proton conductivities are low (10 −7 –10 −6 S cm −1 ) under low relative humidity (RH), and protons mostly migrate as H3 O + with H2 O as vehicles (vehicle mechanism). The proton conductivity of I-A + increases with the increase in RH and is largely dependent on the types of alkali metal ions. I-Li + shows a high proton conductivity of 1.9 × 10 −3 S cm −1 (323 K) and a low activation energy of 0.23 eV under RH 95%. Under high RH, alkali metal ions with high ionic potentials ( e.g., Li + ) form a dense and extensive hydrogen-bonding network of water molecules with mobile protons at the periphery, which leads to high proton conductivities and low activation energies via rearrangement of the hydrogen-bonding network (Grotthuss mechanism).